The impact of natural and simulated herbivory on compensatory leaf production under different light conditions - Twala, Thando Caroline (My University, 2019)
The ability of plants to compensate for disturbances such as herbivory and fire is driven by the type and extent of the disturbance, as well as the availability of resources. In savannas, plants utilise a variety of mechanisms to tolerate disturbances and resource limitations. Compensatory growth, resource reallocation, and photosynthetic and phenological changes have been recognized as mechanisms used by plants to tolerate environmental stress and resource limitation. Herbivory has been extensively researched as one of the main drivers of savanna biomes, but only a few studies have considered the influence of light availability (shading) as a resource affecting plant establishment and recruitment, in particular during the early stages of tree development. There is a gap in our understanding of how juvenile savanna trees (seedlings and saplings) tolerate shade, with many studies considering light as a limiting resource in forests and not in savannas, where light is considered to be a limiting resource to grasses but not woody species. The research that has been conducted on the influence of shading on juvenile trees has neglected how shading affects plant leaf turnover, phenology and leaf traits as well as plant morphology and physiology. Over the past decade only a few seed biology studies have been conducted on Terminalia sericea. These studies were aimed at understanding the seed nutrient content and factors influencing seed germination, but there is still limited information about the main drivers of seed germination, predation and physical properties. The main aims of this study were to: (1) investigate the effect of light availability, as well as natural and/or simulated herbivory on the compensatory growth capabilities of Terminalia sericea, a deciduous broad-leaved savanna tree species of considerable ecological and economical importance, and (2) determine the effect of seed predation and location on samarae (seed) physical properities, as well as the effect of artificial and natural cues on seed germination. The study took place on the roof top of the Oppenheimer Life Sciences Building at the University of the Witwatersrand in Johannesburg, South Africa, over one growing season (September 2016 to May 2017). To investigate the effects of simulated herbivory and light availability (shading) on leaf turnover, longevity and phenology, two pairs of adjacent leaf clusters were selected from the canopies of seedlings and saplings in the sun and 80% shade. On each pair, one cluster was exposed to simulated herbivory (removing 50% of the leaf area along the mid-rib vein) while the adjacent cluster was left untouched. Leaf turnover and longevity were measured at three week intervals and leaf phenology (i.e. timing of leaf age/development classes, e.g. new, fully expanded, mature and senescent) was measured monthly. The herbivory treatments did not affect leaf turnover or phenology. However, simulated herbivory had an effect on leaf longevity in seedlings although not in saplings, with leaf longevity being higher in control leaves compared to herbivory treatment leaves. Shading resulted in lower leaf production and loss, and longer leaf longevity. In addition, there was a higher proportion of new and fully expanded leaf phenophases in full sunlight compared to the shade, with the shade not having an effect on the proportion of mature and senescent leaf phenophases. Although, leaf production was lower in seedlings compared to saplings, the leaves of seedlings quickly matured but delayed leaf senescence, being shed only after the sapling canopy was bare, this is termed phenological avoidance which is an adaptative strategy used to maximise light interception and gain carbon. The influence of shading on Terminalia sericea seedling and sapling architecture, storage reserves (dry mass and allocation patterns), and leaf traits was also tested. This study provided evidence that saplings were larger (taller, higher stem diameter, canopy area and volume as well as biomass), thus indicating that storage reserves increase with an increase in plant stage. Plants grown in the shade allocated more resources to their leaves than sun plants which invested more resources in their roots and shoots. This strategy is used to maximise light capture in the shade through the presence of more leaves (greater leaf size (i.e. length, width, area and thickness)), whereas the high allocation of resources to roots and shoots is an indication that plants were adapted to obtain more water, which is a more important resource in full sunlight, because sunlit plants have higher leaf temperatures and tend to lose more water through transpiration than those in the shade. On saplings in the sun (only) two pairs of leaf clusters were selected on each plant and chlorophyll content (using the SPAD 502-Plus and CCM-300) and stomatal conductance were measured. Phalera imitata, Druce (Notodontidae) larvae were placed on one cluster in each pair with the adjacent cluster left untouched and both clusters were bagged. Phalera imitata larvae were removed after 24 hours and chlorophyll content and stomatal conductance were measured 3 days after herbivory. On the same leaves exposed to simulated herbivory (above) leaf chlorophyll content (measured using the SPAD 502-Plus and CCM-300), stomatal conductance and maximum efficiency of photosystem II (Fv/Fm) were measured at 3 week intervals. Phalera imitata larvae herbivory did not have an effect on chlorophyll content and stomatal conductance on herbivory treatment and control leaves. Simulated herbivory did not have an effect on stomatal conductance and Fv/Fm, however, there were variable chlorophyll content results measured with the different devices, where chlorophyll was not influenced by simulated herbivory when using the CCM-300, but control leaves had higher chlorophyll content than herbivory treatment leaves in seedlings only. Chlorophyll content and Fv/Fm were higher in shaded compared to sun leaves, however, stomatal conductance was higher in sun leaves in seedlings. Shading, however, did not have an effect on stomatal conductance in saplings. Overall, seedlings performed better in the shade than in sunlight and saplings were able to grow well in the sun and shade. I also investigated the influence of seed (samara) predation on seed dimensions from seeds collected from Nylsvley Nature Reserve (Nylsvley) and the Skukuza region of Kruger National Park (Skukuza), as well as the seed germination responses of T. sericea under different natural (temperature and photoperiod) and artificial (soaking and scarification) environmental cues. Seed predation was very site specific, with seed predation having an influence on seed dimensions in Nylsvley and not Skukuza. This suggested that seed predation likely occurred during seed development at Nylsvley, whereas it was post-dispersal at Skukuza. From the germination experimental trial, it was observed that soaking seeds in water at ambient temperature (control), nicking the seeds and germinating them at 12/12h photoperiod resulted in higher levels of seed germination, however, overall seed germination was very low due to overall low seed viability. This dissertation has shown that light should no longer be ignored as a limiting resource in savannas, because it affects many plant responses, particularly during juvenile plant stages. This study has also shown that in order to propagate T. sericea from seed, photoperiod (12/12h), seed soaking (control) and nicking are techniques that promote seed germination. My study has also again highlighted the low viability of T. sericea seeds.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, In partial fulfilment of the requirements for the degree of Master of Science, Johannesburg, South Africa January 2019